Hands of Destiny - Odunwo, Thelma (Evans Brothers (Nigeria Publishers) Ltd, 1988)
Omatsola Temietan is the true son of his indomitable father in the areas of positive ambition,discipline and strong determination. This combination of virtues exposes him to a murder attempt which he narrowly escapes. This attempt becomes a turning point in Omatsola's life, as it brings in fate which heals a wound that has been over thirty-five years old.
Keywords: Juvenile Fiction